Virtual reality sports auxiliary training system based on embedded system and computer technology - Zhou, Jian (Microprocessors and microsystems, 2021)
Virtual Reality technology, the complex environment can be a simulated, traditional sports courses at the stadium, equipment, it is due to limitations such as safety, to provide scientific and accurate teaching and learning's, a complex by visualizing the theoretical knowledge in the abstract sport, you can get more technical knowledge. Compared to the traditional physical education activities, simulate sports scene only by generating VR panoramas that cannot be virtual reality technology. Based on this, you can improve the enthusiasm and athletic ability of students effectively. Because of immaturity and high-priced equipment of VR technology, at present, people that education is using unpopular making, carefully virtual reality technology. In this context, we can apply virtual reality technology to sports training, which can obtain more effective training effect. In the first part of this paper, we talk about the research of virtual reality panorama, the second part about the research of virtual reality video, the third part about the application of virtual reality in physical education teaching, and the fourth part is the conclusion and investigation process. In the study, VR, as a new technology, found that you have the prospect of a wide range of applications. As long as it has been used in scientific and rational, you can VR is to promote the level of improvement and sports greatly sports scene. Users can increase users' interest; it can be immersed in a variety of preset virtual locations. Therefore, in the VR device, which allows the user to improve the experience of the VR device, you can interact well in a virtual scene.